Answer:
Step-by-step explanation:
Suppose a generic quadratic equation
To factor this equation, I need to find its roots. Then we use the quadratic formula of:
and
So, for the equation 63x ^ 2-3x-6 we have:
and
So:
and
Finally the polynomial is:
Answer:
8
Step-by-step explanation:
Number = 2x
Therefore, 2x + 8 = 8(x - 5)
2x + 8 = 8x - 40
6x = 48
<u>x</u><u> </u><u>=</u><u> </u><u>8</u>
you multiply length times width times height.
Answer:
The first law of motion
Step-by-step explanation:
1/3 x (3^-2 x 3^5)
1/3 x (1/3^2 x 243)
1/3 x (1/9 x 243)
1/3 x 27
9